The Role of Leadership in Integrating Human Resource Management, Finance, and School Facilities - Marsa; Tiara Aulia (Journal of Strategy and Transformation in Educational Management, 2026)
This study examines the strategic role of leadership in integrating human resource management, financial governance, and school facility administration to enhance institutional effectiveness and educational quality. Educational organizations operate through interconnected management systems that require coordinated planning, implementation, and evaluation. Using a qualitative systematic literature review combined with comparative institutional analysis, this research evaluates how leadership practices influence teacher development, financial accountability, and infrastructure optimization. The findings indicate that leadership integration fosters organizational synergy, improves staff performance, strengthens financial transparency, and ensures sustainable facility utilization. Transformational and strategic leadership models were found to be particularly effective in aligning resource allocation with educational goals. Despite challenges such as budget limitations, unequal infrastructure distribution, and human resource capacity gaps, integrated leadership frameworks significantly contribute to resilient and future-ready educational institutions.